Analysis of the Relationship Between Intellectual Capital and Firm Performance: An Empirical Research on Borsa Istanbul - Mesut Dogan; Mustafa Kevser (PressAcademia Procedia: Istanbul Finance Congress, November 5-6, 2020, 2020)
Purpose: The purpose of this research is to reveal the effect of firms' intellectual capital on financial performance. Firms invest in intangible assets as well as tangible assets in order to gain competitive advantage (Atan ve Tuncer, 2019). Within the scope of intangible fixed assets, the most investment is made to intellectual capital. Intellectual capital has three basic dimensions: human capital, structural capital and customer capital (Soylu, 2020). In the 21st century, where technology changes and develops very rapidly, companies create added value by using their intellectual capital and turn the added value into profit. In this respect, intellectual capital is knowledge that can turn into profit (Çetin, 2005). Methodology: The intellectual capital levels of companies operating in the Borsa Istanbul Industrial Index were measured by the Intellectual Value Added Coefficient (VAIC) method for the period of 2015-2019. The relationship between the obtained coefficient and financial performance indicators, return on assets ratio (ROA), return on equity (ROE) and Tobin's Q ratio, was analyzed by panel data method. Findings: According to the results of the research, there is a statistically significant and positive relationship between the intellectual capital coefficient and profitability rates and Tobin's Q ratio. Conclusion- The results obtained show the positive effect of intellectual capital on firm performance. Companies can focus on intellectual capital investments and increase their productivity for sustainable financial performance.
Keywords: C61; E22; G30; 330; Intellectual capital; ROA; ROE; Tobin's Q; intellectual value added coefficient